Catalyst-Free Pyrolysis of Mixed Tyres and Plastic Waste for Heavy Fuel-Oil Production with Distillation - Janter Pangaduan Simanjuntak; Mohamad Yusof Idroas; Tosawat Seetawan; Mohd Zamri Zainon (Automotive Experiences, 2025)
Waste from used tires and plastics poses a significant environmental challenge due to their non-biodegradable nature. These materials take hundreds to thousands of years to decompose naturally. Every year, plastic and tire waste increase in correlation with population growth and vehicle usage. This waste management is frequently insufficient, resulting in significant adverse effects on human society. One of the effective solutions to the environmental challenges posed by used tires and plastic waste is converting them into crude oil and solid char using pyrolysis technology without a catalyst. This process is a thermochemical decomposition that occurs at high temperatures without oxygen. Pyrolysis breaks down the complex chemical structure of plastics and tires into simpler, valuable components. After being cut into small pieces of 3 cm to 5 cm, the feedstock was placed into a pyrolyzer, with each batch weighing 500 grams, to produce pyrolytic liquid oil and char. The pyrolysis temperature was set at 350 â„ƒ for all experiments, with a heating rate of 10 â„ƒ/min and a holding time of 90 minutes. The process was followed by distillation at two different temperatures, 250 â„ƒ and 350 â„ƒ, with a heating rate of 10 â„ƒ/min. This distillation process separated the pyrolytic oil based on its boiling points to obtain distillate liquid oil. Two types of distillate liquid oil were produced and analyzed using gas chromatography and mass spectrometry to determine their chemical composition and compounds. It was found that both distillate oils contained similar organic compounds, primarily consisting of complex mixtures of C12”“C31 hydrocarbons, which are typical of heavy fuel oils. The heating value of both distillate oils was 31.26 MJ/kg. Additionally, the residual char produced during the process had a calorific value of 21.73 MJ/kg, indicating its potential use as a solid fuel. These properties demonstrate the potential of the products to substitute conventional fuels for heavy machinery or industrial boilers. This study confirms that used tires and plastic waste can be converted into heavy fuel oils, offering great potential as alternative energy sources.